QHAPAQ ÑAN, LIVING HERITAGE - Chirinos Portocarrero, Ricardo (2014)
This is an essay which attempts to outline the meaning and importance of Inca roads over time in the Andes, from the heyday of Tawantinsuyu until present times. We part from field and gabinet work experience under Qhapaq Ñan Project, between 2009 and 2011. Based on archaeological records achieved between Huánuco Pampa and Huamachuco in the Chinchaysuyu route, we describe some features of the architectural infrastructure, the variability and the functionality of roads and settlements that form the road network, as well as its relationship with the different spanning landscapes, considering the pragmatic and symbolic perspective that conditioned its implementation. Similarly, the anthropological study of contemporary Andean peoples bordering the Qhapaq Ñan, in their socio-economic and cultural features, demonstrates the validity of the Inca trails in modern times, providing guidelines for consistent management of this heritage.